A family with mental retardation, variable macrocephaly and macro-orchidism, and linkage to Xq12-q21. Issue 12 (December 1998) - Johnson, J P; Nelson, R; Schwartz, C E
Abstract : A family with X linked inheritance of mental retardation (XLMR) is presented. There are 10 mentally retarded males and two affected females in two generations. There are four obligatory carriers, one of whom is described as "slow". Most affected males show macrocephaly and macro-orchidism, which are typical signs of the fragile X syndrome, but have been tested cytogenetically and by analysis of the FMR1 gene and do not have this syndrome. However, some normal males in the family also exhibit macro-orchidism and macrocephaly. Linkage analysis using markers derived from the X chromosome indicates that the causative gene in this family is located in the proximal long arm of the X chromosome, in the interval Xp11-q21. Maximum lod scores of 2.96 with no recombination were found at three loci in Xq13-q21: DXS1111, DXS566, and DXS986. Recombination was observed with DXS1002 (Xq21.31) and DXS991 (Xp11.2), loci separated by about 30 Mb. Although isolation of the gene in this family will be difficult because of the size of the region involved, the localisation should be helpful in investigating other similar families with XLMR, macrocephaly, and macro-orchidism not attributable to FMR1.